Religion, Peace and Human Rights: Thematic Interpretation Perspective of the Indonesian Ministry of Religious Affairs - Firmansyah, Rizki; Budi Jaya Putra (Universitas Ahmad Dahlan, 2024)
Religion, peace, and human rights are three very important and complex topics. Religion often provides moral guidance, values, and meaning in life for many people. Besides being a source of strength, peace, and solidarity, it can also cause division if differences are not faced with tolerance. Peace is a harmonious state where conflicts are resolved without violence. Peace is often achieved through dialogue, understanding, and cooperation. Human rights are basic principles that guarantee every individual inalienable rights, such as freedom, equality, and dignity. The three are closely interconnected. When human rights are respected and protected, peace is more likely to be achieved, and religion can play a positive role in building a more just and harmonious society. This study aims to reveal a limited picture of the thematic interpretation of the Indonesian Ministry of Religious Affairs (Depag) regarding peace and human rights in its efforts to make religion a source of harmony among people, both nationally and globally. The method used in this study is qualitative, focusing on the thematic interpretation of the Indonesian Ministry of Religious Affairs (Depag) regarding Peace and Human Rights with a text analysis approach. From this study, it was found that the thematic interpretation by Depag provides guidance for its readers to always practice religion moderately so that the peaceful values of Islam can always be embodied in the actions of every Muslim.